Caristi's Fixed Point Theorem and Subrahmanyam's Fixed Point Theorem in ν-Generalized Metric Spaces. (18th May 2015) - Alamri, Badriah; Suzuki, Tomonari; Khan, Liaqat Ali
Abstract : We discuss the completeness ofν -generalized metric spaces in the sense of Branciari. We also prove generalizations of Subrahmanyam's and Caristi's fixed point theorem.